Inflammatory disease status and response to TNF blockade are associated with mechanisms of endotoxin tolerance - Taylor, PC; Clanchy, FIL; Borghese, F; Bystrom, J; Balog, A; Penn, H; Hull, DN; Williams, RO; Mageed, RA (Elsevier, 2024)
The mechanisms of endotoxin tolerance (ET), which down-regulate inflammation, are well described in response to exogenous toll-like receptor ligands, but few studies have focused on ET-associated mechanisms in inflammatory disease. As blocking TNF can attenuate the development of ET, the effect of anti-TNF on the expression of key ET-associated molecules in inflammatory auto-immune disease was measured; changes in inflammatory gene expression were confirmed using an ET bioassay. The expression of immunomodulatory molecules was measured in a murine model of arthritis treated with anti-TNF and the expression of ET-associated molecules was measured in whole blood in rheumatoid arthritis (RA) and ankylosing spondylitis (AS) patients, before and after therapy. The expression of ET-associated genes was also measured in RA patient monocytes before and after therapy, in anti-TNF responders and non-responders. Tnfaip3, Ptpn6 and Irak3 were differentially expressed in affected paws, spleens, lymph nodes and circulating leucocytes in experimental murine arthritis treated with anti-TNF. Prior to therapy, the expression of TNFAIP3, INPP5D, PTPN6, CD38 and SIGIRR in whole blood differed between human healthy controls and RA or AS patients. In blood monocytes from RA patients, the expression of TNFAIP3 was significantly reduced by anti-TNF therapy in non-responders. Prior to therapy, anti-TNF non-responders had higher expression of TNFAIP3 and SLPI, compared to responders. Although the expression of TNFAIP3 was significantly higher in RA non-responders prior to treatment, the post-treatment reduction to a level similar to responders did not coincide with a clinical response to therapy.